Watching wildlife in Cabo Polonio, Uruguay: tourist control or auto-control? - Tuneu Corral, Carme (2017)
Cabo Polonio (Uruguay) is a popular but atypical centre for beach vacations, because tourists spend days without electricity, running water and vehicle. There is a continental pinniped colony that acts as secondary attraction, but there is not direct control over tourist visits to the rookery. Our objective was to evaluate the experience of visitors to this pinniped colony. We used questionnaires to determine the information used by tourists and to analyse their attitudes towards the colony conservation. To validate questionnaires, we also conducted direct observations of the tourist-pinniped interactions. Less than 15% of tourists received information, which was provided by local people. Most tourists saw the rookery as an important touristic attraction. There was total consensus about the requirement for wildlife information. Despite the lack of active supervision, most people behaved properly and complied with conservation measures: the probability that a tourist crossed the fence during a visit was only 0.002 (17 crosses in 902 hours). This positive attitude is possible related to the fact that tourists in Cabo Polonio, accept the discomfort of living without social commodities and welcome the closeness with nature. It is expected that most people will have a spontaneous predisposition to take care of nature.